Awareness of Contact Lens Related Ocular Complications among Opticians of Lahore: Doi: 10.36351/pjo.v37i4.1262 - Sohail, Ahmed; Abideen, Zain Ul; Zahid, Fatima; Bakhsh, Wahid (Pakistan Journal of Ophthalmology, 2021)
Purpose: To determine the awareness regarding contact lens related ocular complications among opticians of Lahore and to find out the relationship between the awareness and their educational qualification. Study Design: Cross sectional survey. Place and duration of Study: University of Lahore from April 2020- December 2020. Methods: This survey included opticians of different areas of Lahore, Pakistan. Two hundred and eleven opticians responded to a pre-tested, structured close ended questionnaire. Data comprised of demographics and contact lens selling experience. Information regarding awareness about contact lens related complications was also sought. The data were analyzed using SPSS 25.0. Results: A total of 211 opticians participated in the survey. All subjects were males. Fifty four (25.6%) subjects were from the age group of 15 to 30 years, 122 (57.8%) were from the age group of 31 to 45 and 35 (16.6%) were from the age group of 46 to 60 years. Only 4.7% had contact lens dispensing diploma. Thirty seven percent patients had contact lens selling experience of 2 to 10 years. Similar percentage had more than 10 years of experience. Ten percent had less than one year of experience. Only 54 participants out of 211 had knowledge about dry eye, 9 knew about Acanthamoeba keratitis and Bacterial keratitis and only 2 were aware of corneal opacity. Conclusion: Majority of the opticians of Lahore are unaware of the contact lenses related complications. Sale of cosmetic lenses for fashion purpose should be discouraged and banned if not prescribed by optometrist/ ophthalmologist. Key Words: Opticians, Contact lenses, Bacterial Keratitis.